The Impact of Global Warming on Agriculture: A Ricardian Analysis: Reply - Mendelsohn, Robert; Nordhaus, William (American Economic Review, 1999)
The Impact of Global Warming on Agriculture: A Ricardian Analysis: Reply by Robert Mendelsohn and William D. Nordhaus. Published in volume 89, issue 4, pages 1053-1055 of American Economic Review, September 1999